Beneficial Outcomes of Omega-6 and Omega-3 polyunsaturated fatty acids on malnourished children: a scoping review - Mohd Fauzy @ Mohd Ali, Nur Kamilah; Haris @ Harith, Muhammad Salahuddin; Ibrahim, Azrulein; Muhd Helmi, Muhd Alwi; Harith, Sakinah (UPM Press, 2023)
Polyunsaturated fatty acids (PUFAs) intake may be beneficial in many aspects during the early phase of life. This scoping review aims to examine the beneficial outcomes and intakes of omega-3 and omega-6 PUFA among children. An electronic database search on academic journals published from 2017 to 2021 was conducted using Science Direct, PubMed, and Google Scholar. A total of 35 studies were identified and included in this scoping review. Majority of the findings found that PUFAs intake has a beneficial impact on the growth development, mental and cognitive health among children whether they are malnourished, sick or healthy individuals. Overall, this review may provide additional information on the benefits and recommended intake of supplementing PUFAs on children. More detailed research on this topic is needed to support these findings since it will contribute to the formation of the dietary intervention.